Legal Issues of Paylater in the Marketplace - Nurhilmiyah, Nurhilmiyah (Indonesian Journal Education, 2024)
Paylater services in the marketplace have grown rapidly as an alternative to credit-based payments without a card. However, this financing model raises various legal issues, including regulatory aspects, consumer protection, and fairness in determining interest and fees. This study analyzes the legal framework of Paylater in Indonesia, including regulations of the Financial Services Authority (OJK), Bank Indonesia (BI), and consumer protection in digital transactions. The study also compared Paylater regulations in several countries to identify best practices. In addition, the study explores potential legal risks, such as misuse of personal data, cost transparency, and billing practices. The results of the study show that existing regulations still have gaps in controlling aspects of fairness and risk mitigation for consumers. Therefore, stricter policies are needed to increase the transparency and accountability of Paylater services in order to realize an inclusive and equitable digital financial ecosystem.